BOOKTUBERS: uma nova face da crítica literária jornalística - Marchetto, Arthur Breccio (2019)
The dissertation makes a study about the booktubers and the new configurations of the literary journalistic criticism. The historical context is constructed according to the perspective of Zygmunt Bauman and Stanley Fish. The establishment of literature as a cultural text is shaped by a dialogue between Antonio Candido and Iuri Lotman and, together with Mauro Ventura, presents the idea of a journalistic criticism, whose priority is the mediation of the artistic work with the public. Based on in-depth semi-structured interviews with six booktubers, six-month production surveys and reviews of video reviews, the paper looks at how cultural criticism about literature is structured on YouTube and what relationships the booktubers establish with the publishing market and with the public and in what way they structured their sphere of production as a legitimate place of literary discussion.